Pengaruh Pola Agitasi pada Reaksi Transesterifikasi Minyak Jelantah Warung Pecel Lele Menggunakan Katalis Kitosan - Tatang Shabur Juliantoa, Thorikul Huda (EKSAKTA: Journal of Sciences and Data Analysis, 2013)
Effect of agitation on the transesterification reaction of waste cooking oil from pecel lele food stalls around UII campus using chitosan catalyst. Transesterification reaction was done by adding 46 grams of chitosan and 123 mL metanol tothe reactor. The mixture was stirred for 30 minutes to distribute methanol into chitosan. Furthermore,500 mL (460 grams) of cooking oil (= 0.916 g / mL) was add into reactor and agitated at 65oC within two hours using 30 rpm speed . Agitation was performed with several variations of the direction of stirring , one way stirring, stirring 2 ways round the turn at intervals of 5, 10 and 15 minutes. The results show that only 49,95% methyl ester yieldwas obtained (methyl palmitate, methyl-9-octadecenoate , methyl-3-oxooctadecanoate), produced by one directional rotation. Two ways agitation gives methyl ester results on average by 30.41 % . The number of methyl ester was decreased when treated with two way stirring well in intervals of 5 seconds (30.34 %) , 10 seconds (29.97 %) and 15 seconds (30.94 %). Methyl ester product was only sligtly, presumably because the raw material is very bad used cooking oil. It can be indicated from thehigh acid number 8.11 mg/L. and the number of chemical components in addition to triglycerides which may interfere with or hinder the contact between the reactants (chitosan , methanol and triglycerides).Keywords: used cooking oil, chitosan, agitation, transesterification, methyl ester